Implementation of an Application-Based Goods Sales System at the Mitra Berkah Pemangkat Shop - Hartono, Rudi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Doing the basic food business is a business that is always alive, growing and developing, carried out by business actors in the basic food sector because these nine basic ingredients are part of the lives of Indonesian people. Therefore, basic food stores are mushrooming everywhere, present in communities both in rural and urban areas. More familiarly, the basic food stores don't seem to be far away because every few hundred meters there is a basic food shop or stall. Even in people's markets or traditional markets, most of the grocery stores serve their customers side by side. Grocery stores play a role in the process of economic growth among the lower middle class. These basic foodstuffs or nine basic commodities are very familiar to Indonesians. This anonymous word is very unique for foreigners and they quickly understand this unique word. The needs of these nine basic ingredients can be met when they are available in nearby shops and will make consumers anxious if they are not available in basic food stores. Therefore, the presence of grocery stores is very important in moving the wheels of the economy. to meet household expenses. This research uses descriptive quantitative research aimed at exploring the management of basic food businesses by traditional-based traders and technology-based traders.